Cartel Stability with Time-dependent Detection Probabilities - J. Hinloopen (Tinbergen Institute, 2003)
To account for the illegal nature of price-fixing agreements, detection probabilities are introduced in a dynamic oligopoly. It follows that for a trigger strategy to sustain a non-cooperative collusive equilibrium as a SPNE both the discount rate and all per-period detection probabilities have to be `low enough'. Also, the domain reduces for which strictest incentive compatibility constraint is binding of the concomitant non-stationary supergame if (i) any per-period detection probability increases, (ii) prospective fine payments are increased, (iii) the period of limitation is reduced for violating antitrust laws.
Keywords: L12; L41; 330; Cartel stability; trigger strategy; detection probabilities; period of limitation; Kartell; Oligopol; Theorie